2012
DOI: 10.5433/1679-0359.2012v33n6p2451
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores de estresse e qualidade da carne em frangos abatidos pelo método “Halal”

Abstract: ResumoEste trabalho teve como objetivo avaliar o estresse e a qualidade da carcaça e da carne de frangos abatidos pelo método "Halal". Foram avaliadas 120 carcaças, 60 frangos abatidos pelo método tradicional e 60 frangos abatidos pelo método "Halal", com peso médio de 3,8 kg de peso vivo e idade de 49 dias. No momento da sangria foi coletado sangue para análise dos níveis de creatina fosfoquinase, lactato e hemograma. Após o abate foi verificado nas carcaças a presença de hematomas, contusões, hemorragias mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
0
4
1
5
Order By: Relevance
“…The average of the flocks was subjected to statistical analysis using Tukey's test, which showed significant difference (p < 0.05) only in water loss for dripping (WLD). The results obtained in the present paper, was higher than the value found by Bridi et al (2012), who found 3.81% in chicken meat, and Woelfel et al (2002), who found 3.32%, also in chickens. The high rates of WLD can be justified by differences in methodology.…”
Section: Meat Qualitycontrasting
confidence: 89%
“…The average of the flocks was subjected to statistical analysis using Tukey's test, which showed significant difference (p < 0.05) only in water loss for dripping (WLD). The results obtained in the present paper, was higher than the value found by Bridi et al (2012), who found 3.81% in chicken meat, and Woelfel et al (2002), who found 3.32%, also in chickens. The high rates of WLD can be justified by differences in methodology.…”
Section: Meat Qualitycontrasting
confidence: 89%
“…Bridi & Silva (2012) determined CK values of 18.962 U/L and 17.705 U/L in broilers slaughtered by Halal and conventional methods, respectively.…”
Section: Evaluation Of Physiological Parameters Of Broilers With Dorsmentioning
confidence: 99%
“…The C* parameter indicates the degree of color saturation of the meat. Using Pearson's correlation analysis, Bridi et al [27] reported a negative correlation between the pH 24h value and the C* value. In general, in the present study, the effects of the experimental diets on pH 24h were not reflected in the C* value, except for the breast of the broilers fed diet containing soybean oil, which resulted concomitantly in the highest pH 24h value and in the lowest C*.…”
Section: Discussionmentioning
confidence: 99%